Indonesian Pencak Silat Cultural Diplomacy: Analysis of the Spread Persaudaraan Setia Hati Terate - Rahman, Nabil Athaur; Mahdi, Imam (Borong Newinera Publisher, 2025)
This study analyzes the role of Persaudaraan Setia Hati Terate (PSHT) as an instrument of Indonesian cultural diplomacy in Japan in the period 2014-2025. Using a qualitative approach with case studies, this study examines how PSHT has succeeded in becoming an intercultural bridge that strengthens Indonesia's soft power through the spread of pencak silat. The results show that the special Japanese branch of PSHT, which was officially established in 2017 in Osaka, has experienced significant growth with the number of members reaching 412 in 2018 and continuing to grow until 2025. PSHT's cultural diplomacy strategy of combining pencak silat with the Reog Ponorogo performance has proven effective in attracting the interest of the Japanese people, including indigenous people who actively join as members. PSHT's success is supported by the synergy between state actors such as the Indonesian Consulate General in Osaka and the Indonesian Embassy in Tokyo with the Indonesian diaspora community and non-governmental organizations. PSHT's participation in various prestigious events such as UNESCO and the Indonesia-Japan Friendship Festival, as well as the holding of the PSHT Japan Cup, proves the effectiveness of pencak silat as a medium of cultural diplomacy that is able to transcend geographical and cultural boundaries. This study concludes that PSHT has succeeded in creating a positive image of Indonesia as a country with high-value cultural wealth, while strengthening the foundation of Indonesia-Japan bilateral relations through an authentic and sustainable people-to-people connection approach.